Pituitary and periphery : communication in and out - Strasburger, Christian J (BioScientifica, 2003)
A collection of papers presented at a symposium that focused on the pituitary disease and the pituitary hormone. Intended for professional public.
HypoCCS series, ISSN 1466-4151 volume 7
Keywords: růstový hormon; hypofýza; nemoci hypofýzy; Growth Hormone; Pituitary Gland; Pituitary Diseases; endokrinologie